SWOT Analysis of PSBB Policy Implementation at Public Facilities or Areas In Bekasi City in March-June 2020 - Dwijayani, Lidya (Journal of Indonesian Health Policy and Administration, 2021)
: The government of Bekasi City has released specific policies related to PSBB, which started from April 15, 2020, until the fifth amendment that will be over on July 2, 2020, due to the high prevalence of confirmed COVID-19 cases in Bekasi City. Methods: Our study using a combination approach between Media Content Analysis for collecting the secondary data and SWOT analysis plus Trias Policy Analysis in evaluation and identification the role of several elements related to specific policies released from the Government of Bekasi City. Result: There are some best recommendations based on our SWOT analysis and Trias Policy Analysis, such as 1) “New normal” behavior of PHBS in Bekasi City community through health promotion enhancement programs on RT/RW; 2) Reinforcement of regulation and punishment for the violator of PSBB in region area of Bekasi City, and 3) Partnership optimization with social media as the tool of the policy socialization process that released from the government. Conclusion: The effectiveness of policy implementation on PSBB in Bekasi City requires active collaboration among government, community, and media. The participation of government through clarity of policy content, participation of people was through policy compliance, and the media act as the bridging to provide accessible information for the community.